Analysing the Challenges in Enforcement of Data Protection Laws in Uganda - Daphine Kayeki (Uganda Christian University, 2025)
The Data protection and Privacy 2019 was enacted to regulate the collection, Processing and storing of personal data and to also provide rights to data subjects. This study defines different key terms that will be used within the dissertation such as data, personal data, data protection among others. Despite of the enforcement of data protection laws in Uganda there has been significant challenges like lack of sufficient funding to effectively monitor and enforce compliance, limited access to advanced digital tools for investigating data break, non compliance with the laws among others.This study explores the key obstacles hindering effective enforcement including legal and regulatory gaps, institutional weakness, limited public awareness, and technological challenges . It examines the role of regulatory bodies such as the National Information Technology Authority -Uganda ( NITU-U) and assesses their capacity to enforcement compliance and the role of the Data Protection officer (DDPO) in enforcement of the DPPA. This study also assesses other supportive laws and regulations like the computer misuse Act 2011, Access to information Act 2005 and Electronic Transactions Act 2011 among others. Additionally, the study analyses case studies and draws comparisons with other jurisdictions such as the EU General Data protection Regulations (GDPR) to highlight best practices that Uganda can adopt to strengthen data protection enforcement like adoption of regulations and possibly amending some areas of the law, Data protector or processor reporting compliance with the law. The findings reveal that inadequate resources, lack of technical expertise and weak enforcement mechanisms contribute to poor data protection. The study recommends strengthening legal framework, enhancing institutional capacity, increasing public awareness and investing in digital infrastructure to improve enforcement. Therefore by addressing these challenges, Uganda can ensure better compliance with data protection regulations, thereby safeguarding personal data in an increasingly digital economy.